Evaluation of Hazardous and Toxic Waste (B3) Management at PT. X, North Jakarta - Sri Winda Astuti (Fakultas Teknik - Universitas Satya Negara Indonesia, 2025)
The management of hazardous and toxic waste (B3) requires strict compliance with technical and administrative regulations. This study aims to evaluate the B3 waste management system at PT. X in North Jakarta and assess its conformity with the applicable regulatory standards. The research utilized secondary data obtained from the company’s Technical Details Document (Rintek) of the Temporary B3 Waste Storage Facility. Data collection was conducted through documentation review, and evaluation was performed using a checklist instrument based on the Guttman scale scoring system. Three key technical aspects were assessed: storage, packaging and containment, and symbol and label attachment. The results showed scores of 96% for storage, 100% for packaging and containment, and 87.5% for labeling, with an overall average of 94.5% (classified as “Excellent”). Key findings included the absence of an automatic fire detection system and incomplete labeling on waste container lids. Based on clarifications with the environmental consultant, it was concluded that PT. X’s B3 waste management complies with regulations but still requires improvements in safety equipment and administrative labeling.